Field-deployable RspCas13d platform for rapid and extraction-free detection of giant panda- and canine-derived Canine Distemper virus - Qian Tao; Yuxiao Xing; Haidi Yang; Linhua Deng; Ming He; Yanxi Cheng; Qian Wang; Zhan Gao; Haohong Wan; Desheng Li; Shanshan Ling (Analytica Chimica Acta, 2026)

Intraperitoneal extracellular trap-derived proteins mediate the amplification of vaccine-induced immune responses in flounder (Paralichthys olivaceus) - Jiahui Zhang; Qian Li; Xiaoqian Tang; Chengxu Ha; Jing Xing; Xiuzhen Sheng; Wenbin Zhan; Heng Chi (Fish & Shellfish Immunology, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

The regulatory role of HIRRV nucleoprotein on STING-mediated interferon response - Pingyuan Sun; Wenshuo Li; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2026)

Exploring the potential mechanism of GABA in the treatment of abdominal aortic aneurysm through network pharmacology and experimental validation - Lu-Zhe Huang; Li-Li Chen; Jian-Jun Wang; Xi-Guan Du; Xiong-Ying Zhang; Fang-Wei Zhan; Jun-Xing Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Biochar nanoparticles modulate root-associated microbial interactions under polycyclic aromatic hydrocarbon stress - Yu Shen; Hao Su; Dongru Wang; Hui Huang; Jiangang Han; Hui Li; Melanie Kah; Xinhua Zhan; Baoshan Xing (Journal of Environmental Management, 2026)

Seasonal dynamics and interfacial exchange of parent and alkylated polycyclic aromatic hydrocarbons in a subtropical lake: Overlooked alkylated derivatives involved a shift in ecological risk assessment - Tianpeng Hu; Yufei Zhang; Yao Mao; Xiu Li; Ying Liu; Mingming Shi; Min Guo; Changlin Zhan; Ziguo Liu; Xinli Xing; Shihua Qi (Environmental Research, 2026)

Improved masculinization effect induced by letrozole via suppression of the feminization through AMH signaling in mandarin fish (Siniperca chuatsi) - Kai Yang; Xing Chen; Jiankang Bao; Gang Zhai; Xuehui Li; Hongfei Bao; Xia Jin; Jiangyan He; Huijie Wei; Yin-ai Gao; Zhan Yin; Qiyong Lou (Aquaculture, 2026)

Sparteine-type alkaloids with anti-tomato spotted wilt virus from the seeds of Lupinus angustifolius L. - Jian-Guo Tan; Cheng-Feng Liu; Li Wang; Xing-Ya Wu; Li-Hua Zhao; Xiao-Jiang Hao; Zhan-Xing Hu (Pesticide Biochemistry and Physiology, 2026)

Cytochrome P450-mediated detoxification and NF-κB/NLRP3 pathway-driven hepatotoxicity of emodin: Multiomics and laboratory evidence - Lili Wu; Siyu Chen; Qiyuan Yang; Xing Li; Lingyan Liu; Shengjun Ji; Shuaiyuan Tang; Sihui Zhang; Yan Wang; Runzhi Chen; Zhikun Zhan (Chemico-Biological Interactions, 2026)

Joint impact of heat and ozone exposure on mortality in Henan, central China - Dong Ding; Kai Kang; Shaofang Li; Tianfang Xing; Wenjie Yang; Liuqiao Sun; Xinxin Liu; Yao Chen; Mingyi Xue; Zengli Yu; Zhan Gao (Atmospheric Environment, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Competitive effect-derived surface-enhanced Raman scattering for analysis of glutathione based on a gold nanotriangle-modified nanocapillary - Kan Zhan; An-Ni Bao; Yi-Ling Li; Zhao-Xiang Li; Yuan-Shan Wang; Hai-Ling Liu; Kang Wang; Xing-Hua Xia (Analytica Chimica Acta, 2026)

Mechanism of earthworm coelomic fluid inhibits multidrug-resistant bacteria and blocks resistance transmission - Lihan Lin; Jingwen Luo; Zhan Li; Hongan Guo; Tao Liu; Xiaojie Sun; Meiyan Xing (Environmental Pollution, 2025)

Study on the Response of Soil Microbial Communities to Different Nitrogen Application Rates in ‘Korla Fragrant Pear’ Orchards - Zeyue Ma; Xuemei Wang; Lei Feng; Wei Li; Zhan Huang; Minghao Sun; Xing Shen; Zhongping Chai (Applied Fruit Science, 2025)

Denitrification dominates nitrate attenuation and nitrous oxide effluxes under water table fluctuations - Lin Zhang; Helin Wang; Xiaohan Liu; Hongbin Zhan; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Yanfeng Liu; Ping Li (Journal of Hazardous Materials, 2025)

Investigating fracture response characteristics and fractal evolution laws of pre-holed hard rock using infrared radiation: Implications for construction of underground works - Ze-Kun Zhang; Jin-Xing Lai; Zhan-ping Song; Yong-Li Xie; Jun-ling Qiu; Yun Cheng; Le Zhang (Tunnelling and Underground Space Technology, 2025)

Effects of environmentally relevant concentrations of carbendazim, either alone or combined with benzophenone-3, on testicular development in Xenopus laevis - Jie Li; Hai-Ming Xu; Xing-Hong Li; Yuan-Yuan Li; Zhan-Fen Qin (Aquatic Toxicology, 2025)

Carbon dioxide reduction through mineral carbonation by steel slag - Yongpeng Zhang; Yimei Ying; Lei Xing; Guoxiong Zhan; Yanli Deng; Zhen Chen; Junhua Li (Journal of Environmental Sciences, 2025)

Chemosensory protein 8 confers thiamethoxam resistance in Diaphorina citri - Qian Li; Wan-Wei Hu; Ao Fang; Zhuo-Bing Wang; Xiao-Fang Yuan; Yue Sun; Zheng-Hui Zou; Nuo Chen; Tian-Xing Jing; Ying-Xue Liu; Wei Chen; Hai-Zhong Yu; et al. (Pesticide Biochemistry and Physiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Proteomic and phosphoproteomic analyses reveal the biological perturbations caused by capsaicin treatment - Zicang Li; Meining Xing; Wenhao Hou; Zhan Yue; Ying Jiang; Wantao Ying (Food Research International, 2025)

Multi-stage magma emplacement in the western end of the Jinchuan Ni Cu sulfide deposit, NW China, and mineral exploration strategy based on exploration data - Long-Jiao Li; Xian-Cheng Mao; Zhan-Kun Liu; Xin-Ming Duan; Yun-Qi Wang; Qi-Xing Ai; De-Xian Li (Journal of Geochemical Exploration, 2025)

Evaluating the impact of dermal absorption on internal doses of dechlorane plus in Chinese e-waste recycling employees - Yao-Yuan Wan; Xiao-meng Cheng; Xing-Hong Li; Feng-Shuang Wang; Yuan-Yuan Li; Jing Li; Zhan-Fen Qin (Chemosphere, 2024)

Super-large diameter slurry shield tunnel encountering boulder formation: Detection, treatment and data analysis - Wei-Hong Yang; Dong Su; Xing-Tao Lin; Zhi-Jia Lv; Zhan-Hu Yao; Hui Li; Ya-Zhou Zhang; Xiang-Sheng Chen (Transportation Geotechnics, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Simulation and optimization for flue gas CO2 capture by energy efficient water-lean ionic liquid solvent - Guoxiong Zhan; Zhen Chen; Lei Xing; Bingling Yuan; Zhoulan Huang; Xuebing Liu; Yongpeng Zhang; Jianjun Chen; Junhua Li (Chemical Engineering Journal, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Comprehensive investigation of a dangerous counter-tilt landslide in the upper reaches of Jinsha River, China - Qiang Xu; Zhigang Li; Weihua Zhao; Weile Li; Xing Zhu; Xiujun Dong; Congwei Yu; Weimin Li; Xueqing Li; Xincheng Wang; Huiyan Lu; Shouyu Wang; et al. (Landslides, 2024)

Impact of earthworms on suppressing dissemination of antibiotic resistance genes during vermicomposting treatment of excess sludge - Hongan Guo; Zhan Li; Xiaojie Sun; Meiyan Xing (Bioresource Technology, 2024)

Extracellular traps in skin lesions infected with lymphocystis disease virus in black rockfish (Sebastes schlegelii) - Qian Li; Qiujie Gan; Heng Chi; Xianghu Meng; Roy Ambli Dalmo; Xiuzhen Sheng; Xiaoqian Tang; Jing Xing; Wenbin Zhan (Fish & Shellfish Immunology, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Clinically relevant immune subtypes based on alternative splicing landscape of immune-related genes for lung cancer advanced PPPM approach - Na Li; Wenshuang Jia; Jiahong Wang; Qianwen Shao; Xiaoxia Feng; Zhijun Li; Wenhao Sun; Ming Kang; Dongming Hu; Ligang Xing; Xianquan Zhan (EPMA Journal, 2024)

The Sirtuin 5 Inhibitor MC3482 Ameliorates Microglia‑induced Neuroinflammation Following Ischaemic Stroke by Upregulating the Succinylation Level of Annexin-A1 - Qian Xia; Yongbo Yu; Gaofeng Zhan; Xue Zhang; Shuai Gao; Tangrui Han; Yilin Zhao; Xing Li; Yonghong Wang (Journal of Neuroimmune Pharmacology, 2024)

Organic carbon in wet deposition of an urbanized coastal bay, North China: Flux, sources and biogeochemical implications - Chenlong Feng; Jianwei Xing; Huamao Yuan; Jinming Song; Xuegang Li; Tianrong Zhan; Jun Ma (Marine Pollution Bulletin, 2024)

Variation of chalcophile elements in base metal sulfide minerals from the Jinchuan magmatic Ni–Cu sulfide deposit, NW China: Implications for mineral exploration - Long-Jiao Li; Xian-Cheng Mao; Zhan-Kun Liu; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Yun-Qi Wang (Journal of Geochemical Exploration, 2024)

Performance and mechanisms of alkaline solid waste in CO2 mineralization and utilization - Yongpeng Zhang; Guoxiong Zhan; Zhoulan Huang; Lei Xing; Yimei Ying; Zhen Chen; Junhua Li (Waste Management, 2024)

Elimination of antibiotic-resistant bacteria and resistance genes by earthworms during vermifiltration treatment of excess sludge - Meiyan Xing; Ran Zhao; Gege Yang; Zhan Li; Yuzhu Sun; Zitao Xue (Environmental Science and Pollution Research, 2024)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Facile preparation of biocompatible and antibacterial water-soluble films using polyvinyl alcohol/carboxymethyl chitosan blend fibers via centrifugal spinning - Bowen Zhang; Zhan Jiang; Xing Li; Zhiyu Wu; Yuemei Liu; Jun Hu; Chunhua Zhang; Junyi Chen; Yingshan Zhou; Jue Rao; Xin Liu (Carbohydrate Polymers, 2023)

Rapid reduction of aqueous Cr(VI) by oxalic acid on N-doped lignin charcoal: A significant contribution of structural defects and electronic shuttle effect - Mingxin Li; Hongling Dai; Peng Zhan; Chaoqun Tan; Zhihui Ning; Fengping Hu; Xing Xu; Xiaoming Peng (Journal of Cleaner Production, 2023)

Influence of seasonal water-level fluctuations on depth-dependent microbial nitrogen transformation and greenhouse gas fluxes in the riparian zone - Lin Zhang; Yanfeng Liu; Menggui Jin; Xing Liang; Stefan Krause; Uwe Schneidewind; Yiming Li; Hongbin Zhan (Journal of Hydrology, 2023)

New dimeric sesquiterpenoids from the whole plant of Artemisia sieversiana - Jun-yi Dong; Yu-xing Cai; Ya-lin Li; Yu-xin Zhang; Zhan-peng Yu; Ling-yi Kong; Jian-guang Luo (Phytochemistry Letters, 2023)

In-situ preparation of yeast-supported Fe0@Fe2O3 as peroxymonosulfate activator for enhanced degradation of tetracycline hydrochloride - Bin Li; Chen-Xuan Li; Yan Wang; Weiyi Xu; Kangping Cui; Xinyuan Zhan; Rui Deng; Xing Zhang (Chemosphere, 2023)

An efficient green-emitting quantum dot with near-unity quantum yield and suppressed Auger recombination for high-performance light-emitting diodes - Xiaokun Fan; Zhen Mu; Zhao Chen; Yunfeng Zhan; Fanyuan Meng; Yang Li; Guichuan Xing; Wai-Yeung Wong (Chemical Engineering Journal, 2023)

Mechanochemically activated microscale zero-valent iron with carboxymethylcellulose for efficient sequestration of phosphate in aqueous solution - Wenjuan Shen; Zhan Liu; Fengjiao Quan; Xu Zhang; Xing Peng; Xiaobing Wang; Wenqing Wang; Lan Huang; Shunxi Zhang; Jianfen Li; Yunjun Mei (Journal of Environmental Chemical Engineering, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Streptomyces griseicoloratus sp. nov., isolated from soil in cotton fields in Xinjiang, China - Li Xing; Ying-ying Xia; Qiao-Yan Zhang; Zhan-Feng Xia; Chuan-xing Wan; Li-li Zhang; Xiao-Xia Luo (Archives of Microbiology, 2022)

Two bicistronic DNA vaccines against Vibrio anguillarum and the immune effects on flounder Paralichthys olivaceus - Hanlin Li; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Oceanology and Limnology, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Theoretical and Numerical Analysis of Blasting Pressure of Cylindrical Shells under Internal Explosive Loading - Zhan-Feng Chen; Hui-Jie Wang; Zhiqian Sang; Wen Wang; He Yang; Wei-Ming Meng; Yu-Xing Li (Journal of Marine Science and Engineering, 2021)
Cylindrical shells are principal structural elements that are used for many purposes, such as offshore, sub-marine, and airborne structures. The nonlinear mechanics model of internal blast loading was established to predict the dynamic blast pressure of cylindrical shells. However, due to the complexity of the nonlinear mechanical model, the solution process is time-consuming. In this study, the nonlinear mechanics model of internal blast loading is linearized, and the dynamic blast pressure of cylindrical shells is solved. First, a mechanical model of cylindrical shells subjected to internal blast loading is proposed. To simplify the calculation, the internal blast loading is reduced to linearly uniform variations. Second, according to the stress function method, the dynamic blast pressure equation of cylindrical shells subjected to blast loading is derived. Third, the calculated results are compared with those of the finite element method (FEM) under different durations of dynamic pressure pulse. Finally, to reduce the errors, the dynamic blast pressure equation is further optimized. The results demonstrate that the optimized equation is in good agreement with the FEM, and is feasible to linearize the internal blast loading of cylindrical shells.

Crustal deformation characteristics in the southwest segment of the Longmenshan structural belt before Lushan Mw6.6 earthquake and seismogenic structural model - Dongzhuo Xu; Shenghu Li; La Ta; Sanming Luo; Wei Zhan; Wenwu Zhu; Xing Shen (Acta Geophysica, 2021)

A Lagrangian study of the near-surface intrusion of Pacific water into the South China Sea - Gaolong Huang; Haigang Zhan; Qingyou He; Xing Wei; Bo Li (Acta Oceanologica Sinica, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Efficient CRISPR/Cas9-mediated gene editing in Guangdong small-ear spotted pig cells using an optimized electrotransfection method - Yan-yan Wei; Qun-mei Zhan; Xiang-xing Zhu; Ai-fen Yan; Juan Feng; Lian Liu; Jian-hao Li; Dong-sheng Tang (Biotechnology Letters, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Nitrogen and phosphorus co-addition stimulates soil respiration in a subtropical evergreen broad-leaved forest - Shengzhao Wei; Liehua Tie; Jiao Liao; Xing Liu; Meilin Du; Suxin Lan; Xiaorui Li; Chengsong Li; Haichuan Zhan; Congde Huang (Plant and Soil, 2020)

Technological behavior of the early Late Pleistocene archaic humans at Lingjing (Xuchang, China) - Hao Li; Zhan-yang Li; Xing Gao; Kathleen Kuman; Alexandra Sumner (Archaeological and Anthropological Sciences, 2019)

Application of carotenoid to alleviate the oxidative stress caused by phenanthrene in wheat - Yu Shen; Jinfeng Li; Shengnan Shi; Ruochen Gu; Xinhua Zhan; Baoshan Xing (Environmental Science and Pollution Research, 2019)

Seasonal variation and health risk assessment of atmospheric PM2.5-bound polycyclic aromatic hydrocarbons in a classic agglomeration industrial city, central China - Tianpeng Hu; Jiaquan Zhang; Xinli Xing; Changlin Zhan; Li Zhang; Hongxia Liu; Ting Liu; Jingru Zheng; Ruizhen Yao; Junji Cao (Air Quality, Atmosphere & Health, 2018)

Phytotoxic, antibacterial, and antioxidant activities of mycotoxins and other metabolites from Trichoderma sp. - Ju-cheng Zhang; Guang-Yi Chen; Xiao-Zhan Li; Ming Hu; Bang-Yan Wang; Bao-Hui Ruan; Hao Zhou; Li-Xing Zhao; Jun Zhou; Zhong-Tao Ding; Ya-Bin Yang (Natural Product Research, 2017)

Remote sensing retrieval of surface suspended sediment concentration in the Yellow River Estuary - Chao Zhan; Junbao Yu; Qing Wang; Yunzhao Li; Di Zhou; Qinghui Xing; Xiaojing Chu (Chinese Geographical Science, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

High genetic diversity and absence of phylogeographic structure in breeding populations of vulnerable Saundersilarus saundersi (Charadriiformes: Laridae) in Bohai Bay, China - Ya-Nan Zhang; Bo-Ye Liu; Lu Dong; Hong-Xing Jiang; Xuan Wang; Xue-Min Wang; Chang-Zhan Song; Xiu-Ming Li; Shu-Hong Li (Conservation Genetics, 2017)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Identification of Genes Involved in the Biosynthesis of Tripterygium wilfordii Hook.f. Secondary Metabolites by Suppression Subtractive Hybridization - Guo-peng Miao; Wei Li; Bin Zhang; Zhan-feng Zhang; Zhi-qing Ma; Jun-tao Feng; Xing Zhang; Chuan-shu Zhu (Plant Molecular Biology Reporter, 2015)

A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Molecular characterization and tissue localization of sensory neuron membrane protein from Chinese honey bee, Apis cerana cerana (Hymenoptera: Apidae) - Ying-Ying Hu; Shu-Fa Xu; Abebe Jenberie Wubie; Wei Li; Jia-Xing Huang; Zhan-Bao Guo; Ting Zhou (Applied Entomology and Zoology, 2013)

A slowly proliferating subpopulation in human umbilical cord mesenchymal stem cells in culture - Xing-Ai Ju; Jin Chen; Li Ding; Yu-Zhi Li; Feng-Jun Xiao; Zhan-Quan Li; Zi-Kuan Guo (In Vitro Cellular & Developmental Biology - Animal, 2013)

Large-scale gold mineralization in eastern China induced by an Early Cretaceous clockwise change in Pacific plate motions - Weidong Sun; Shuang Li; Xiaoyong Yang; Mingxing Ling; Xing Ding; Liu'an Duan; Meizhen Zhan; Hong Zhang; Weiming Fan (International Geology Review, 2013)

Hydro-mechanical experiments on suffusion under long-term large hydraulic heads - Yu-long Luo; Liang Qiao; Xing-xing Liu; Mei-li Zhan; Jin-chang Sheng (Natural Hazards, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Selenomethionine: an Effective Selenium Source for Sow to Improve Se Distribution, Antioxidant Status, and Growth Performance of Pig Offspring - Xiuan Zhan; Yanzhao Qie; Min Wang; Xing Li; RuQian Zhao (Biological Trace Element Research, 2011)

Effect of Different Selenium Sources on Productive Performance, Serum and Milk Se Concentrations, and Antioxidant Status of Sows - Huijuan Hu; Min Wang; XiuAn Zhan; Xing Li; RuQian Zhao (Biological Trace Element Research, 2011)

The construction of siRNA plasmid targeting mouse HIF-1α and in vitro study of its inhibition effect - Zhen-Yu Ding; Ze-Gui Li; Yi-Zhan Xing; Hua Ji; Hong-Li Li; Zhi-Jie Chang (Neuroscience Bulletin, 2009)

Hematological changes in white spot syndrome virus-infected shrimp, Fenneropenaeus chinensis (Osbeck) - Shouming Feng; Wenbin Zhan; Jing Xing; Jun Li; Kai Yang; Jing Wang (Journal of Ocean University of China, 2008)

Microsatellite Analysis of Genetic Variation and Population Genetic Differentiation in Autotetraploid and Diploid Rice - Li Luan; Xing Wang; Wen-Bo Long; Yu-Hua Liu; Sheng-Bin Tu; Zhan-Peng Zhao; Fan-Lun Kong; Mao-Qun Yu (Biochemical Genetics, 2008)